Pemanfaatan ICT Guru Pendidikan Agama Islam (PAI) dalam Pembelajaran Peserta Didik di SMK PGRI 2 Kediri - Putri Lestari; A. Jauhar Fuad; Abbas Sofwan Matlail Fajar (STIKes Ibnu Sina Ajibarang, 2024)
The more advanced world civilization becomes, the more education will develop and problems will arise that need to be solved. One of them is that there are still PAI teachers who are not fully equipped with the skills to use information technology in PAI learning, resulting in the learning process becoming boring and monotonous, causing class conditions not to be conducive to learning development. In fact, SMK PGRI 2 Kediri has adequate technological facilities such as a sound system, LCD/projector, and computer internet network. This research is qualitative research with a descriptive approach. flow model data analysis techniques which include; data reduction, data presentation, and drawing conclusions. This research has implications for the use of ICT by PAI teachers who emphasize the importance of active learning, collaboration, and the use of diverse learning strategies to meet students' diverse learning needs. The results of this study include 1) Collaborative efforts between innovation diffusion and institutionalization implementation of PAI teachers in utilizing ICT in student learning can be done in several ways. First, PAI teachers can access wider educational resources using ICT, Second, teachers can increase interaction with students, and Third, provide flexibility in learning. In addition, teachers also need to have a collaborative friendly attitude, be creative, take risks, and conduct comprehensive learning so that the learning process can run effectively. Thus, PAI teachers can be more effective in using ICT to improve the quality of learning and improve student learning outcomes. 2) The role of policies and regulations in supervising and facilitating PAI teachers in utilizing ICT in learner learning includes determining curriculum and pedagogical standards, providing infrastructure and conducting evaluation and monitoring.